A cross sectional questionnaire based study of knowledge, attitude and practices of pharmacovigilanceprogramme among staff nurses in a teaching tertiary care hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
BackgroundSince the inception of Pharmacovigilanceprogramme (PVP) in our institution spontaneous reporting of adverse drug reactions (ADRs) has been minimal. Under reporting of ADRs is a known fact due to variable knowledge, attitude and practices (KAP) of healthcare professionals which prompted us to know the KAP of nursing staff in our institution.Material and MethodsA questionnaire based cross sectional study using a pre designed set of questions. Study included 134 staff nurses from government medical college and associated hospitals Srinagar J&K India.ResultsOur study using KAP questionnaire revealed that in knowledge based questions 59% participant were aware of the health care professional responsible for reporting ADR, 70% were aware of PVP, 11% were how to fill ADR form, 38% were knowing ADRs of which drugs to be reported and 27% were knowing the time period within which a serious ADR needs to be reported. All attitude based questions scored high on attitude based questions. Contrary to expectations from knowledge and attitude of participating staff nurses the practice of ADR reporting was very poor.ConclusionThere is a need for curriculum development in order to impart teaching and hands on training to improve knowledge and practices of ADR reporting